FDI, industrialisation and environmental quality in SSA—the role of institutional quality towards environmental sustainability - John Abdulai Jinapor; Joshua Yindenaba Abor; Michael Graham (Humanities & Social Sciences Communications)
Abstract In light of the quest to achieve economic development without compromising environmental quality, we empirically examine whether institutional quality (INSQY) can help moderate the possible harmful effects of foreign direct investments (FDI) and industrialisation on environmental quality in sub-Saharan Africa (SSA). We utilise the Driscoll and Kraay standard error estimation technique on a panel of 45 SSA countries from 2000 to 2019. The results indicate that FDI and industrialisation generally have a significant harmful effect on the environment. Our findings reveal that INSQY directly promotes environmental quality. Notably, the results confirm that INSQY plays a stimulating role in mitigating the adverse effects of FDI and industrialisation on environmental quality. The results further validate the environmental Kuznets curve (EKC) hypothesis in SSA. These findings contribute to environmental sustainability literature and offer policymakers insights on how INSQY can enhance environmental quality. Our empirical results are also robust to different estimation techniques, such as the two-stage least squares. We recommend SSA leaders strengthen institutional capacities, enforce environmental regulations, and implement strict policies to ensure environmental quality while promoting industrialisation and FDI inflows.